Lowered Immune Cell Function in Liver Recipients Recovered From Posttransplant Lymphoproliferative Disease Who Developed Graft Tolerance. Issue 3 (March 2016) - Chung, Patrick Ho Yu; Chan, See Ching; Chan, Kwong Leung; Chan, Yuk Sing; Kwok, Janette Siu Yin; Lo, Chung Mau
Abstract : Introduction: Tolerance after treatment and recovery from posttransplant lymphoproliferative disease (PTLD) have been described but little is known about the immunology. The objective of this study is to evaluate the immunity of pediatric recipients who recovered from PTLD. Materials and Methods: Pediatric recipients who recovered from PTLD after liver transplant and twice the number of recipients who never had PTLD were recruited. Their immune statuses were measured by ImmuKnow (measurement of adenosine 5-triphospate level produced CD4+ T helper cells), and the results were divided into 3 groups, "low" (⩽225 ng/mL), "moderate" (226 to 524 ng/mL), and "high" (≥525 ng/mL). The results of both groups were compared and analyzed. Results: Nine PTLD recipients and 20 non-PTLD recipients were recruited. There were no significant differences in terms of sex and age between the 2 groups. The majority of PTLD recipients (88.9%) had "low" immune status responses, and none of them had "high" responses. For non-PTLD recipients, more than half (55%) had "moderate" immune status responses. The median value of adenosine 5-triphospate levels was significantly lower in the PTLD group (119 ng/mL vs 380.5 ng/mL P = 0.014), and their trough immunosuppressant level was also lower (3.8 μg/L vs 7.7 μg/L; P = 0.004). None of the patients in either group had abnormal liver enzymes (aspartate aminotransferase/alanine aminotransferase) to suggest graft rejection. Conclusions: Patients who recovered from PTLD have a lower CD4 T-cell activity compared with those who have not suffered from PTLD. Under careful monitoring, their immunosuppressant levels can be kept at low levels to prevent recurrence of PTLD.